1971
DOI: 10.1098/rstb.1971.0001
|View full text |Cite
|
Sign up to set email alerts
|

The corpora pedunculata of Sphinx Ligustri L. and other Lepidoptera: an anatomical study

Abstract: The corpora pedunculata, or mushroom bodies, are paired lobes of neuropile present in the protocerebrum or dorsal brain of all insects. They are divisible into three parts: calyx, stalk and roots. The latter usually comprise two simple lobes, the a and ft lobes. The corpora pedunculata of a variety of Lepidoptera were examined. All had a double calyx-cup. Each ‘cup-cavity’ is composed of ‘globuli’ cell bodies. The broad stalk, a tract of fibres and neuropile, leads from the calyx to the complex ‘roots’—a, g an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 8 publications
1
33
0
Order By: Relevance
“…Similar sensory afferents have been reported in orthopteran (Ignell et al, 2001), dipteran (yellow fever mosquito, Aedes aegypti: Ignell et al, 2005) and lepidopteran insects (Pearson, 1971), including the larval moth Manduca sexta (Kent and Hildebrand, 1985), and are thought to be mechanosensory neurons (Ignell et al, 2001. Detailed observation by confocal microscopy in the cockroach, however, has shown that the sub-tract consists of several dozen thin axons and axon terminals having numerous microglomerular structures.…”
Section: Evolutionary Conservation Of T9 and T10 Glomerulimentioning
confidence: 85%
“…Similar sensory afferents have been reported in orthopteran (Ignell et al, 2001), dipteran (yellow fever mosquito, Aedes aegypti: Ignell et al, 2005) and lepidopteran insects (Pearson, 1971), including the larval moth Manduca sexta (Kent and Hildebrand, 1985), and are thought to be mechanosensory neurons (Ignell et al, 2001. Detailed observation by confocal microscopy in the cockroach, however, has shown that the sub-tract consists of several dozen thin axons and axon terminals having numerous microglomerular structures.…”
Section: Evolutionary Conservation Of T9 and T10 Glomerulimentioning
confidence: 85%
“…The mushroom bodies of Pieris consist of the calyx, consisting of two fused saucer-like structures located posterior and dorsal in the butterfly brain, and the anteriorly-located lobes [Nordlander and Edwards, 1968;Pearson, 1971;Ali, 1974]. These two parts are connected by a thin stalk, which can be seen in figure 1 b, but which was not included in our measurements because of its small size.…”
Section: Brain Regions and Measurementsmentioning
confidence: 99%
“…Our measurements focused on the calyces and the lobes, which were the most easily delineated parts of the mushroom body. Mushroom body lobes have several parts in the Lepidoptera [e.g., alpha, beta, gamma; Pearson, 1971;Ali, 1974], but are not easy to discriminate, thus we measured the lobes together.…”
Section: Brain Regions and Measurementsmentioning
confidence: 99%
“…Recently, Schü rmann et al (2000) described differences in the glutamatelike immunoreactivity in subpopulations of cricket Kenyon cells. The structure of the lobes also reflects Kenyon cell heterogeneity in different insect species (Goll, 1967;Pearson, 1971;Schä fer et al, 1988;Schü rmann and Erber, 1990;Bicker, 1991;Elphick et al, 1995;Brotz et al, 1997;Strambi et al, 1998;Strausfeld and Li, 1999;Strausfeld et al, 2000;Farris and Strausfeld, 2001;Sinakevitch et al, 2001). However, extensive studies demonstrating the development of the laminar organization in mushroom bodies are still rare.…”
mentioning
confidence: 93%